Entropic risk for turn-based stochastic games - Baier, Christel; Chatterjee, Krishnendu; Meggendorfer, Tobias; Piribauer, Jakob (Information and Computation)
Entropic risk (ERisk) is an established risk measure in finance, quantifying risk by an exponential re-weighting of rewards. We study ERisk for the first time in the context of turn-based stochastic games with the total reward objective. This gives rise to an objective function that demands the control of systems in a risk-averse manner. We show that the resulting games are determined and, in particular, admit optimal memoryless deterministic strategies. This contrasts risk measures that previously have been considered in the special case of Markov decision processes and that require randomization and/or memory. We provide several results on the decidability and the computational complexity of the threshold problem, i.e. whether the optimal value of ERisk exceeds a given threshold. Furthermore, an approximation algorithm for the optimal value of ERisk is provided.

Constant-time dynamic weight approximation for minimum spanning forest - Henzinger, Monika H; Peng, Pan (Information and Computation)
We give two fully dynamic algorithms that maintain a (1 + ε)-approximation of the weight M of a minimum spanning forest (MSF) of an n-node graph G with edges weights in [1, W ], for any ε > 0. (1) Our deterministic algorithm takes O (W 2 log W /ε3) worst-case update time, which is O (1) if both W and ε are constants. (2) Our randomized (Monte-Carlo style) algorithm works with high probability and runs in worst-case O (log W /ε4) update time if W = O ((m∗)1/6/log2/3 n), where m∗ is the minimum number of edges in the graph throughout all the updates. It works even against an adaptive adversary. We complement our algorithmic results with two cell-probe lower bounds for dynamically maintaining an approximation of the weight of an MSF of a graph.

Dynamic algorithms via the primal-dual method - Bhattacharya, Sayan; Henzinger, Monika H; Italiano, Giuseppe (Information and Computation)
We develop a dynamic version of the primal-dual method for optimization problems, and apply it to obtain the following results. (1) For the dynamic set-cover problem, we maintain an O ( f 2)-approximately optimal solution in O ( f · log(m + n)) amortized update time, where f is the maximum “frequency” of an element, n is the number of sets, and m is the maximum number of elements in the universe at any point in time. (2) For the dynamic b-matching problem, we maintain an O (1)-approximately optimal solution in O (log3 n) amortized update time, where n is the number of nodes in the graph.

Doomsday equilibria for omega-regular games - Chatterjee, Krishnendu; Doyen, Laurent; Filiot, Emmanuel; Raskin, Jean (Information and Computation)
Two-player games on graphs provide the theoretical framework for many important problems such as reactive synthesis. While the traditional study of two-player zero-sum games has been extended to multi-player games with several notions of equilibria, they are decidable only for perfect-information games, whereas several applications require imperfect-information. In this paper we propose a new notion of equilibria, called doomsday equilibria, which is a strategy profile where all players satisfy their own objective, and if any coalition of players deviates and violates even one of the players' objective, then the objective of every player is violated. We present algorithms and complexity results for deciding the existence of doomsday equilibria for various classes of ω-regular objectives, both for imperfect-information games, and for perfect-information games. We provide optimal complexity bounds for imperfect-information games, and in most cases for perfect-information games.

38th International Colloquium on Automata, Languages and Programming - Aceto, Luca; Henzinger, Monika H; Sgall, Jiří (Information and Computation)

Stack size analysis for interrupt-driven programs - Chatterjee, Krishnendu; Ma, Di; Majumdar, Ritankar; Zhao, Tian; Henzinger, Thomas A; Palsberg, Jens (Information and Computation)
We study the problem of determining stack boundedness and the exact maximum stack size for three classes of interrupt-driven programs. Interrupt-driven programs are used in many real-time applications that require responsive interrupt handling. In order to ensure responsiveness, programmers often enable interrupt processing in the body of lower-priority interrupt handlers. In such programs a programming error can allow interrupt handlers to be interrupted in a cyclic fashion to lead to an unbounded stack, causing the system to crash. For a restricted class of interrupt-driven programs, we show that there is a polynomial-time procedure to check stack boundedness, while determining the exact maximum stack size is PSPACE-complete. For a larger class of programs, the two problems are both PSPACE-complete, and for the largest class of programs we consider, the two problems are PSPACE-hard and can be solved in exponential time. While the complexities are high, our algorithms are exponential only in the number of handlers, and polynomial in the size of the program.

Fair simulation - Henzinger, Thomas A; Kupferman, Orna; Rajamani, Sriram (Information and Computation)
The simulation preorder for labeled transition systems is defined locally, and operationally, as a game that relates states with their immediate successor states. Simulation enjoys many appealing properties. First, simulation has a denotational characterization: system S simulates system I iff every computation tree embedded in the unrolling of I can be embedded also in the unrolling of S. Second, simulation has a logical characterization: S simulates I iff every universal branching-time formula satisfied by S is satisfied also by I. It follows that simulation is a suitable notion of implementation, and it is the coarsest abstraction of a system that preserves universal branching-time properties. Third, based on its local definition, simulation between finite-state systems can be checked in polynomial time. Finally, simulation implies trace containment, which cannot be defined locally and requires polynomial space for verification. Hence simulation is widely used both in manual and in automatic verification. Liveness assumptions about transition systems are typically modeled using fairness constraints. Existing notions of simulation for fair transition systems, however, are not local, and as a result, many appealing properties of the simulation preorder are lost. We propose a new view of fair simulation by extending the local definition of simulation to account for fairness: system View the MathML sourcefairly simulates system View the MathML source iff in the simulation game, there is a strategy that matches with each fair computation of View the MathML source a fair computation of View the MathML source. Our definition enjoys a denotational characterization and has a logical characterization: View the MathML source fairly simulates View the MathML source iff every fair computation tree (whose infinite paths are fair) embedded in the unrolling of View the MathML source can be embedded also in the unrolling of View the MathML source or, equivalently, iff every Fair-∀AFMC formula satisfied by View the MathML source is satisfied also by View the MathML source (∀AFMC is the universal fragment of the alternation-free μ-calculus). The locality of the definition leads us to a polynomial-time algorithm for checking fair simulation for finite-state systems with weak and strong fairness constraints. Finally, fair simulation implies fair trace containment and is therefore useful as an efficiently computable local criterion for proving linear-time abstraction hierarchies of fair systems.

Temporal proof methodologies for timed transition systems - Henzinger, Thomas A; Manna, Zohar; Pnueli, Amir (Information and Computation)
We extend the specification language of temporal logic, the corresponding verification framework, and the underlying computational model to deal with real-;time properties of reactive systems. The abstract notion of timed transition systems generalizes traditional transition systems conservatively: qualitative fairness requirements are replaced (and superseded) by quantitative lower-bound and upper-bound timing constraints on transitions. This framework can model real-time systems that communicate either through shared variables or by message passing and real-time issues such as timeouts, process priorities (interrupts), and process scheduling. We exhibit two styles for the specification of real-time systems. While the first approach uses time-bounded versions of the temporal operators, the second approach allows explicit references to time through a special clock variable. Corresponding to the two styles of specification, we present and compare two different proof methodologies for the verification of timing requirements that are expressed in these styles. For the bounded-operator style, we provide a set of proof rules for establishing bounded-invariance and bounded-responce properties of timed transition systems. This approach generalizes the standard temporal proof rules for verifying invariance and response properties conservatively. For the explicit-clock style, we exploit the observation that every time-bounded property is a safety property and use the standard temporal proof rules for establishing safety properties.

Symbolic model checking for real-time systems - Henzinger, Thomas A; Nicollin, Xavier; Sifakis, Joseph; Yovine, Sergio (Information and Computation)
We describe finite-state programs over real-numbered time in a guarded-command language with real-valued clocks or, equivalently, as finite automata with real-valued clocks. Model checking answers the question which states of a real-time program satisfy a branching-time specification (given in an extension of CTL with clock variables). We develop an algorithm that computes this set of states symbolically as a fixpoint of a functional on state predicates, without constructing the state space. For this purpose, we introduce a μ-calculus on computation trees over real-numbered time. Unfortunately, many standard program properties, such as response for all nonzeno execution sequences (during which time diverges), cannot be characterized by fixpoints: we show that the expressiveness of the timed μ-calculus is incomparable to the expressiveness of timed CTL. Fortunately, this result does not impair the symbolic verification of "implementable" real-time programs-those whose safety constraints are machine-closed with respect to diverging time and whose fairness constraints are restricted to finite upper bounds on clock values. All timed CTL properties of such programs are shown to be computable as finitely approximable fixpoints in a simple decidable theory.